Sharia Investment in Islamic Economic Principles - Nurti Budiyanti; Aceng Kosasih; Shafa Aulia Az-Zahra (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
Islam encourages its followers to carry out investment activities in order to create an economic increase and equal income. Islam forbids its followers to accumulate wealth for the sake of enriching and selfishness for personal gain. This research uses descriptive research method with secondary data. The results show that not all types of investment are allowed. Investors, especially Muslims, need to know that not all types of investment are allowed in Islam. Investment in accordance with Islamic principles is an investment that is lawful and does not contain elements prohibited by Islam. The types of investment allowed by Islam are mudarabah and musyarakah. Meanwhile, investments that are not allowed by Islam are maisir, gharar, riba, batil, bay'i ma'dium, ihtikar, taghrir, ghabn, talaqqi al-rukban, ghishsh, tanajush / najsh, dharar, rishwah, immorality and wrongdoing. Investment is a muamalah activity which has four kinds of principles in Islam, namely monotheism, Al-'Adl wa al-Ihsan, endeavour, and responsibility. By understanding these principles, investors, especially Muslims, will avoid investment activities that are prohibited by Islam so that they will get the pleasure of Allah SWT and also profit that is lawful.